Acromioaxillosuprasternal notch index(AASI)Versus Traditional Airway Parameters In Predicting Difficult Visualisation Of Larynx - An Observational Study - Bharathi, Thatha Lakshmi; ravulapalli, Harish babu; rekha.S, Vijaya; vandana, Kakani Vishnu; krishna, Yekollu Hari (Journal of Neonatal Surgery, 2025)
Background: Predicting difficult laryngoscopy remains a challenge in anesthesia. The acromio axillo suprasternal notch index (AASI) is a novel, objective test designed for this purpose. AIM: To assess the diagnostic accuracy of AASI in predicting difficult laryngoscopy and compare its performance with other conventional airway predictors: Modified Mallampati Grading (MPG), Sternomental Distance (SMD), and Thyromental Distance (TMD). Methods: This prospective, observational, double-blinded study included 150 patients undergoing elective surgeries under general anesthesia. Preoperative airway assessment included AASI, MPG, TMD, and SMD. The Cormack-Lehane (CL) grading was assessed during direct laryngoscopy. Statistical analysis was performed using ROC curves, sensitivity, specificity, PPV, and NPV calculations. Results: The incidence of difficult visualization of larynx (CL grade 3 & 4) was 33.3%. AASI showed the highest sensitivity (93.3%) and specificity (91.2%) at a cutoff value of >0.49. AUC for AASI was 0.933, outperforming MPG (AUC = 0.765), TMD (AUC = 0.702), and SMD (AUC = 0.728). Conclusion: AASI is a superior predictor for difficult laryngoscopy compared to MPG, TMD, and SMD, offering a simple, reliable, and objective tool, especially useful in supine or uncooperative patients.